Back to school with Bigfoot - Berger, Samantha; Brockenbrough, Martha; Pressler, Dave, 1964- (New York : Arthur A. Levine Books, an imprint of Scholastic Inc., 2017)
The school year is about to start, and Bigfoot is worried about all the things that could go wrong--but he also remembers that all his friends will be there.
Keywords: Sasquatch -- Juvenile fiction; Schools -- Juvenile fiction; Friendship -- Juvenile fiction; Sasquatch -- Fiction; Schools -- Fiction; Friendship -- Fiction; Friendship; Sasquatch; Schools; Picture books; Fiction; Juvenile works